Secondary fault system in Northern Sumatra, evidenced by recent seismicity and geomorphic structure. (15th April 2023) - Muksin, Umar; Arifullah, Arifullah; Simanjuntak, Andrean V.H.; Asra, Nadiatul; Muzli, Muzli; Wei, Shengji; Gunawan, Endra; Okubo, Makoto
Graphical abstract: Highlights: The unknown or less well-known secondary faults in Northern Sumatra either located in the north or in the south of the Sumatran Fault including including the Lokop, Langsa, Batee, and Alas faults have been investigated. The secondary faults are delineated well by the seismicity distribution and geomorphic structure as well as supported by the focal mechanisms. The strike-slip Lokop fault is the most active and even has produced earthquake swarm in 2020. The Langsa fault and thrustfold belt was created because of the compression between Sumatra and the Mergui microplate. Abstract: Several medium-sized inland earthquakes have occurred away from the main Sumatra fault, which indicates the complexity of fault systems in Aceh, Northern Sumatra. The characteristics of these secondary faults in southeast Aceh between Lake Laut Tawar and lake Toba have not been comprehensively studied. The objective of the research was to investigate faults in Aceh using a combination of accurate seismicity, focal mechanisms, and geomorphic structures. Temporary seismic stations were installed in the southeast Aceh to cover several suspected secondary faults to complement the permanent stations. >500 seismic events formed earthquake clusters representing several known but previously unexplored faults. Coupled velocity and earthquake relocation followed by relative relocation were used to improve the location of hypocenters. The relocated seismicity delineates the Tripa segment of the Sumatran fault and the Batee fault, as well as the Langsa and Lokop faults. The distribution of the earthquakes in the southern part of Aceh explains the characteristics of the Batee fault in the NW–SE direction. The Langsa fault and thrustfold belt, evidenced by earthquake mechanisms, was caused by the compression between Sumatra and the Mergui microplate. The seismicity and focal mechanisms as well as the geomorphic lineament confirm that the Lokop fault strikes in NW–SE direction. The Batee NNW–SSW striking faults were created by principal stress nearly perpendicular to the Indian-Sumatra convergence line. In the north, the Lokop fault was created by a similar mechanism to accommodate the horizontal stress caused by compression between Sumatra and the Mergui microplate.